Chloride Diffusivity in Blended Cement Made from Selected Industrial and Agrowastes - Jackson Muthengia Wachira; Joseph Mwiti Marangu (Advances in Materials Science and Engineering)
This paper reports study findings on the diffusivity of chloride ions in potential blended cement. The cement, abbreviated as PCDC, was made from blending ordinary Portland cement (OPC) with dried calcium carbide residue and an incinerated mix of rice husks, spent bleaching earth, and broken bricks. The aim of the study was to investigate the ability of PCDC to withstand aggressive chloride environment. 10 cm × 10 cm mortar cubes were prepared using PCDC and cured for 28 days in saturated calcium hydroxide solution. The cured mortar cubes were subjected to aggressive chloride media in a laboratory set up. The test cement was subjected to chloride profile analysis with depth of cover as a function of w/c ratio and curing period in alternate dry and wet environments of 3.5 percent sodium chloride solution. The experiments were carried alongside neat OPC and OPC + 25% pulverised fuel ash (OPC + 25% PFA). Results showed that PCDC exhibited lower chloride ingress as the depth of cover increased. In conclusion, the study showed that PCDC was a potential cementitious material with high ability to withstand aggressive environment of chlorides.